EFFECT OF DIMENSSION EMPLOYEE WELFARE AGAINTS EMPLOYEE LOYALITY OF BANK INDONESIA MALANG - PAHRIYATUL UMMAH (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to analyze the effect of the dimensions of we being of employee consisting of variable eployee benefits are ecoomic, employee benefits are facilities, and employee are benefits are service influence on employee loyality of Bank Indonesia Malang.This type of research used ini this research is quantitative research. In this study used a sample 50 permanent employee of Bank Indonesia Malang. The number of samples obtained by using saturation sampling technique, so we get the total sample of 50 respondents. The analysis tool used is multiple linier regression and classic assumption test including normality test, test multicolinearity and heterocedasticity test. Then, to test the hypotesis, f test, t test, and the test is dominant. The results of multiple linier regression analysis showed that te welfare of the employee with variable employee benefits characteristically economic and benefits characteristically services no significant effect on loyalty employee. benefits characteristically facility significant effect on loyalty employee. Of the three variables which have a dominan influence on employee loyalty is variable characteristically facility employee benefits. Then, seen from the value of adjusted R Square shows the amount of influence between variables 0,375, which means there is influence between variables benefits characteristically economic, employee benefits characteristically facility and benefits characteristically services to loyalty employee by 37,5% while the remaining 62,5% is explained by variables that are not detected in this study.Keywords : loyalty, loyalty emplyees, emplyee benefits.